(untitled) (Journal of Hama University, 2021)
Diabetes is a global health problem and many factors contribute in its occurrence including environmental factors, life style, family history, ethnicity and heredity. Diabetes as a chronic disease requires a high level of individual responsibility because most of the daily care activities are performed by the patient himself. The aim of the study was to identify the relationship between health locus of control and compliance to self-care activities among diabetic patients. this study was conducted in the diabetes center in latakia. Data collected from 29/5/2020 to 29/7/2020. The sample comprised of (150) diabetes patient. They were chosen by the systematic random sampling method. Three tools were used, the first tool (demographic and clinical data sheet) was been filling by the researcher through a personal interview, then all patients who participated in the study were asked to answer on the second tool (health locus of control scale) and the third tool (self-care activities scale). This study found that there was an inverse significant statistical relationship between external health locus of control (chance) and adherence to self-care activities among diabetic patients, also there was a significant statistical relationship between internal health locus of control and age, level of education, current job, where internal locus of control was higher for older , college-educated patients who currently had a job. So, it is recommended to conduct training courses for medical and nursing staff in diabetes care centers, as well as to use the media, workshops and seminars on unhealthy lifestyle modifications, including healthy nutrition, sport, smoking cessation and weight loss.